Physical Condition Profile of Weightlifters in Banda Aceh City As a basis for performance building - Dicky Imam Bahesty; Santi Sunadari; Mia Melissa (Kodepena Indonesia, 2026)
Physical condition is a fundamental factor that determines the success of athlete development and performance achievement in weightlifting. Effective athlete development requires an objective and measurable assessment of physical condition as a basis for designing appropriate training programs. This study aimed to determine the physical condition profile of weightlifting athletes in Banda Aceh City as a foundation for performance development toward PORA, Pre-PON, and PON competitions. This study employed a quantitative approach with a descriptive research design. The subjects were Banda Aceh City weightlifting athletes selected using a total sampling technique. Data were collected through physical condition tests covering muscular strength, explosive power, speed, flexibility, and muscular endurance. Data analysis was conducted using descriptive statistics, including mean values and classification based on physical condition norms. The results showed that muscular strength was categorized as good with a mean score of 82, while explosive power (75), speed (70), flexibility (68), and muscular endurance (72) were classified as moderate. These findings indicate that the development of weightlifting athletes in Banda Aceh City has been relatively effective in improving strength but still requires further enhancement in supporting physical components. It can be concluded that systematic physical condition profiling is essential as a scientific basis for developing more targeted, individualized, and sustainable athlete training programs. The results of this study are expected to serve as a reference for coaches and sports administrators in improving the quality of weightlifting athlete development in Banda Aceh City.